Current research on cellobiose 2-epimerase: Enzymatic properties, mechanistic insights, and potential applications in the dairy industry. (December 2018) - Chen, Qiuming; Xiao, Yaqin; Zhang, Wenli; Zhang, Tao; Jiang, Bo; Stressler, Timo; Fischer, Lutz; Mu, Wanmeng
Abstract: Background: Over the past decade, substantial advances have been made in the study of cellobiose 2-epimerase (CE). CE participates in the recently discovered mannan metabolism and catalyzes the interconversion of D-glucose residues at the reducing end of mannooligosaccharides. This enzyme also exhibits different degrees of epimerization and isomerization activities towards different saccharides. Scope and approach: This review addresses the latest research on the enzymatic properties, structural information, and technical advances relating to CE. Key findings and conclusions: CE is attractive because this enzyme can convert lactose into its epimeric and isomeric forms, epilactose and lactulose, respectively. Epilactose and lactulose are candidate functional food materials that confer significant economic value to CE in the dairy industry. Although a broad range of CEs from different mesophilic and thermophilic microorganisms have been characterized, the present knowledge about the relationship between the function and structure of CE is limited and not connected to further genetic modifications for potential CE applications. Thus, more attention has been paid to the midstream and downstream processes for industrial applications of CE. A number of studies on CE have been performed to seek out better industrial applications. However, further efforts are needed to understand the underlying enzymatic reaction mechanism and protein engineering to fulfill the full potential of CE. Highlights: Cellobiose 2-epimerase (CE) is an important tool for functional disaccharides production. The enzymatic properties of all reported CEs are comprehensively discussed. Discussed the epimerization and isomerization mechanisms of CEs based on crystal structures. Reported the properties and production methods of two primary CE-involving products, epilactose and lactulose.